Pilot field trial of the EG95 vaccine against ovine cystic echinococcosis in Rio Negro, Argentina: 8 years of work - Larrieu, Edmundo (2019)
Fil: Larrieu, Edmundo. Universidad Nacional de La Pampa. Facultad de Ciencias Veterinarias; Argentina.